2019
DOI: 10.1007/s42421-019-00011-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Algorithms for Revealing Freight Vehicle Tours, Tour-Types, and Tour-Chain-Types from GPS Vehicle Traces and Stop Activity Data

Abstract: Freight vehicle tours and tour-chains are essential elements of state-the-art agent-based urban freight simulations as well as key units to analyse freight vehicle demand. GPS traces are typically used to extract vehicle tours and tour-chains and became available in a large scale to, for example, fleet management firms. While methods to process this data with the objective of analysing and modelling tour-based freight vehicle operations have been proposed, they were not fully explored with regard to the implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Processing FCD to measure RNP is challenging as traffic data can be considered big data due to its complexity and heterogeneity [78,93,94]. However, navigation service providers can produce the needed data efficiently [84].…”
Section: Road Network Data Collection: Developing a New Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing FCD to measure RNP is challenging as traffic data can be considered big data due to its complexity and heterogeneity [78,93,94]. However, navigation service providers can produce the needed data efficiently [84].…”
Section: Road Network Data Collection: Developing a New Methodsmentioning
confidence: 99%
“…For a case-specific analysis, Alho A.R. et al [78] find that declared data regarding bases might not be as accurate as inferred data, suggesting the identification of central network nodes via algorithms instead of relying on survey data to determine meaningful points of origin. Referring to Saedi et al [63] our approach does not report RNP across the complete road network but well-defined partitions.…”
Section: Fundamentals On Road Network Performance Measurementsmentioning
confidence: 99%
“…Romano Alho et al (2019) demonstrated the importance of carefully selecting and disclosing the methods for data processing by illustrating that the predictions of tours, tour types, and tour chains are highly dependent on assumptions. They implement high-resolution tour-chain algorithms for a large-scale GPS-based survey and use stop-level data from a driver survey conducted from 2017 to 2019 in Singapore.…”
Section: Descriptive Applicationsmentioning
confidence: 99%
“…These can support the development of models for simulating freight movements [26,31,32]. In order to identify the vehicle freight activities from GPS data (e.g., stops), algorithms have to be developed [33,34]. Vehicle stop identification is a key aspect faced when analyzing the data, that can be very hard when intermediate short stops (e.g., waiting at traffic lights, congestion) are detected [33,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In this topic, Holguín-Veras et al [34] proposed a procedure based on changes in speed and acceleration to identify the stops of freight vehicles, while Alho et al [33] compared some algorithms developed with the aim of identifying the tour stops. Some methods ( [38,39]) suggest extracting and evaluating vehicle stops by considering engine ignition, others are based on speed ( [40,41]).…”
Section: Introductionmentioning
confidence: 99%